Beyond Type 1 and Type 2: Literature Review of Etiology, Pathophysiology, and Diagnosis of Other Type Diabetes Mellitus - Rabbani, Muhammad Afif; Dwiputri, Adelya Rahma; Putri, Ajeng Ayu; Difa, Anak Agung Gede Agung; Madani, Ayda Fitri; Ramadhani, Dhea Asty; Maolidi, Juan; Rizky, Muhammad Ilham; Faranajhia, Hagia; Zakiyyah, Luthfi; Amatullah, Tazkiyah Arafah; Susani, Yoga Pamungkas (Jurnal Biologi Tropis, 2024)
Diabetes mellitus is a metabolic condition that has been long known for its complexity, with type 1 and type 2 being the main focus on research and clinical practice for decades. This literature review aims to provide a comprehensive understanding of other types of diabetes mellitus other than type 1 and type 2, focusing on recognizing the etiology, pathophysiology, and way of diagnosis for each type of unconventional diabetes mellitus. In addition, this review also includes the identification of risk factors that influence the development of the disease, potential complications, and disease prognosis to provide a comprehensive view of this condition, and finally, a preventive strategies that can be applied is also discussed. The literature search was performed using trusted databases, including PubMed and Google Scholar. The result of this literature review is that diagnosing other type of diabetes mellitus is still challenging, with most still require specific testing for precise diagnosis. Thus, understanding etiology and pathophysiology of this disease will aid in directing health practitioners on which specific testing is needed for patients.